2014
DOI: 10.1016/j.neubiorev.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in idiopathic generalised epilepsies: A systematic review and meta-analysis

Abstract: Cognitive function in idiopathic generalised epilepsies (IGE) is of increasing research attention. Current research seeks to understand phenotypic traits associated with this most common group of inherited epilepsies and evaluate educational and occupational trajectories. A specific deficit in executive function in a subgroup of IGE, juvenile myoclonic epilepsy (JME) has been a particular focus of recent research. This systematic review provides a quantitative synthesis of cognitive function outcomes in 26 pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 45 publications
8
88
1
7
Order By: Relevance
“…These widespread alterations of cortical thickness and volumes beyond the frontal cortex may underlie the neurocognitive deficits in patients with GGE. Loughman et al [15] recently conducted a meta-analysis of neuropsychological tests in patients with GGE. The authors found that the patients with GGE had significantly lower scores on cognitive processing speed, crystallized and fluid intelligence, short-term/working memory, long-term memory retrieval, and overarching generalized cognitive ability, compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These widespread alterations of cortical thickness and volumes beyond the frontal cortex may underlie the neurocognitive deficits in patients with GGE. Loughman et al [15] recently conducted a meta-analysis of neuropsychological tests in patients with GGE. The authors found that the patients with GGE had significantly lower scores on cognitive processing speed, crystallized and fluid intelligence, short-term/working memory, long-term memory retrieval, and overarching generalized cognitive ability, compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts those studies that demonstrated that patients with symptomatic or structural-metabolic etiology have an increased risk of developing neurocognitive deficits. Nevertheless, several authors reported a heightened prevalence of cognitive deficits in genetic epilepsy or idiopathic generalized epilepsy with a strong genetic component as well [35]. The fact that only an unknown etiology contributed significantly to the prediction of EF status prior to AED treatment in the multivariate analysis points to several problems associated with new-onset pediatric epilepsy.…”
Section: Potential Predictors For Ef Deficits At Epilepsy Onsetmentioning
confidence: 99%
“…Epileptiform discharges are abnormal neuronal discharges seen on Electroencephalogram (EEG) as a result of transient synchronous depolarisation of neurons [1]. Findings from published work suggest that these discharges are not mere biomarkers of epilepsy but have important behavioural and cognitive consequences [2][3][4]. Niemann et al established an independent relationship between cognitive impairment and the percentage of epileptiform discharges for a large number of factors such as the duration of epilepsy and the aetiology [5].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that IGE patients demonstrated significantly lower scores on tests across all cognitive factor-domains except visual-spatial abilities [3] and increasing seizure frequency was significantly associated with worse outcomes [19]. Epilepsy is not understood as a disorder affecting one discrete brain region but as a disorder of widespread brain networks [20].…”
Section: Introductionmentioning
confidence: 99%